Insights into the pharmacodynamics and pharmacokinetics of meldonium after exposure to acute high altitude - Liu, Fengying; Sui, Xin; Wang, Qian; Li, Jinglai; Yang, Weijie; Yang, Yi; Xiao, Zhenyu; Sun, Yangyang; Guo, Xiaoxuan; Yang, Xinyi; Yang, Jun; Wang, Yongan; et al. (Frontiers in Pharmacology, 2023)
Meldonium, as a well-known cardioprotective drug, has been reported to be protective against pulmonary injury at high altitudes; however, the pharmacodynamics of meldonium in other vital organs under acute high-altitude injury are less investigated and the related pharmacokinetics have not been fully elucidated. The present study examined the basic pharmacodynamics and pharmacokinetics (PK) in rat exposure to acute high-altitude hypoxia after oral and intravenous pre-administration of meldonium. The results indicate that meldonium can improve acute hypoxia-induced pathological damage in brain and lung tissues, and restore blood biochemistry and routine blood index of heart, liver and kidney tissues under a simulated acute high-altitude environment. Furthermore, compared to the normoxia group, rats exposed to simulated high-altitude hypoxia and premedicated with oral meldonium showed linear kinetics in the dose range of 25-100 mg/kg, with significantly increase in the area under curve (AUC) and half-life and reduced clearance rate. No significant differences in these meldonium PK parameters of were observed with intravenous administration. Additionally, meldonium was involved in the regulation of succinic acid and 3-hydroxypropionic acid. These results will contribute to our understanding of the preclinical PK properties of meldonium and its acute high-altitude protective effects.